Efektifitas Sistem Jalan Underpass untuk Kota Pintar DKI Jakarta - Arman Syah Putra (Jurnal Informatika Universitas Pamulang, 2020)
This study discusses the effectiveness of the Underpass at the red light of Jalan Kramat Kebayoran Lama, South Jakarta, with the builder of the Underpass at the red light at Jalan Kramat Kebayoran, South Jakarta, DKI Jakarta. people come home from work, or in the morning and evening between 07:00 - 10:00 until 16:00 - 19:00, the method used is first by conducting a literature review or literature review study and second by conducting a field study, with doing a literature review then we will get problems from previous studies, with the review of literature can also add knowledge in the matter under study, then by field studies by looking directly at the place under study in order to retrieve accurate data. This underpass is very useful for residents to make it easy to cross to other areas without having to rotate far. In this research, we can find out the effectiveness of the Underpass at the red light of the old Jakarta Kebayoran Kramat Street, Jakarta. Underpas will change the activities of the surrounding community, for example by crossing the road will be further, and can find out what problems can be solved.